KESIAPAN SEKOLAH TINGGI ILMU TARBIYAH (STIT) KOTA PAGAR ALAM DALAM IMPLEMENTASI KURIKULUM YANG MENGACU PADA KERANGKA KUALIFIKASI NASIONAL INDONESIA (KKNI) - Alip Kamaron (IAIN Bengkulu, 2020)
The issuance of Presidential Regulation (Perpres) of the Republic Indonesia Number 8 Year 2012 and the Regula- tion of the Minister of Education and Culture (Permendikbud) Number 73 Year 2013, requires the University to redesign the curriculum referring to the Indonesian Qualification Framework (IQF). IQF is a framework of competency qualification that can match, equalize and integrate between the field of education and the field of job training and work experience in the framework of giving recognition of work competence in accordance with the structure of work in various sectors. This research is to analyze,1). How is the readiness of the board in the implementation of the curriculum to the IQF in Higher Education of Islamic Stud- ies (STIT) Pagar Alam, 2). How is the readiness of lecturers in the implementation of curriculum to IQF in Higher Education of Islamic Studies (STIT) Pagar Alam and 3). How is the readiness of facilities and infrastructure in the implementation of cur- riculum to IQF in Higher Education of Islamic Studies (STIT) Pagar Alam. Qualitative method was used in this research, data collection technique using interview, observation and documentation. The results is showed that readiness of the board in the implementation of the curriculum to IQF in Higher Education of Islamic Studies (STIT) Pagar Alam is still relatively low, it can be seen from some indicators that 1). The management has never attended a workshop, training on the preparation of IQF based curriculum, 2). Never had any socialization regarding curriculum to IQF, and 3). Do not have a guide for curriculum IQF. The readiness of lecturers in the implementation of curriculum to IQF in Higher Education of Islamic Studies (STIT) Pagar Alam is also still low and not ready, it can be seen from the lack of understanding of lecturers about curriculum IQF, teaching system which is conveyed by lecturers still tend to be conventional. In terms of facilities and infrastructure can be said is sufficient in the implementation of a curriculumIQF.